Bahasa Inggris - Putri Nur Wandah; Fadillah, Jihad; Firzaly, Zalfa Anindhiya; Asri, Sarly (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2024)
This study investigates the impact of diverse learning styles on listening comprehension abilities among English education students in a university in Bandung, Indonesia. Utilizing a descriptive qualitative research design, the research involved 10 participants who underwent learning style tests, with in-depth interviews conducted on three selected participants. The findings revealed a spectrum of learning styles. Interviews provided valuable insights into the strategies employed by each learning style, such as visual learners favoring videos and seeking additional explanations online. Auditory learners preferred expert explanations and quiet study environments, while kinesthetic learners utilized movement during group discussions. Classroom observations demonstrated the effectiveness of tailored strategies, incorporating visual aids, auditory elements, and hands-on activities to create an inclusive learning space. The result underscored the significance of multimodal approaches for maximizing student engagement and comprehension. It is recommended for educators to recognize diverse learning styles, employ flexible instructional methods, and foster inclusive learning environments. Hence, the research reinforces the notion that educators should recognize the presence of various learning styles, actively adopt adaptable teaching approaches, and foster inclusive learning environments, thus optimizing student involvement and understanding.